1HRDP.Ver2: Effective administrative tool towards lean productivity / Intan Syahriza Azizan ... [et al.] - Azizan, Intan Syahriza; Ismail, Junaida; Ahmad Zawawi, Azlyn; Rusli, Noorayuni; Ahmad, Afida (2021)
The "1 Hour Report Duty Process Version 2 (1HRDP.Ver2)" is developed to establish a report duty process via web application for new lecturers to be used in UiTM Kedah Branch. A manual report duty is a practice that requires sufficient space and involves cost in purchasing office cabinets or racks for administration purposes which involves a lot of time and energy. A new lecturer had to go to many departments to complete the process, and they had to deal with many levels of bureaucracy. A manual process also involves hardcopy documents that are easily corrupted, lost, or damaged if not kept properly. The 1HRDP.Ver2 system enhances the process of report duty activities via an online system that aims to shorten the time taken to complete the registration process in an organized and efficient manner. Simultaneously, the 1HRDP.Ver2 creates a database that keeps all report duty documents and data in one repository, indirectly reducing clerical or administrative tasks. The 1HRDP.Ver2 aims to become a center of report duty database that administrators and new lecturers can rely upon. The 1HRDP.Ver2 system utilized the Design Thinking approach, which empowers innovation to value functionality in organizational design, as we move to the digitalization era. The results of the 1HRDP.Ver2 system development had achieved significant reductions in terms of cost and time. The new lecturers are guided to complete the report duty process within 1 hour with the improved process. The process is designed in the form of an easy-to-understand and navigable web application. There is an easy access function to important information, aiming to assist users in completing the report duty process. Users will also have information on the person in charge in each department. Documents that previously were unable to be filled online can now be filled up in real-time. The system will then direct users to respective departments through external links that can be reached through computers or smartphones. In a nutshell, the 1HRDP.Ver2 application is an organized web-based system or application that is designed to maintain long-term access to digital data, which significantly increases efficiency in data/record management. The system is an organization's information asset. It increases customer satisfaction as it can be easily reached at users' fingertips, enabling UiTM Kedah to achieve a "green-university" status by adopting a digital web application for its administrative process.